Effectiveness of Archive Management at the Office of the Education Quality Assurance Agency of South Sulawesi Province - Muhammad Darwis; Yessica Claresta; Jamaluddin Jamaluddin; Nasaruddin H; Muh. Nasrullah (Universitas Negeri Makassar, 2022)
Archives have a role as a memory center, as a source of information, and as an indispensable monitoring tool in every organization. This study aims to determine the effectiveness of archive management at the Office of the Education Quality Assurance Agency/Lembaga Penjaminan Mutu Pendidikan (LPMP) of South Sulawesi Province. To achieve this goal, the researchers set 5 (five) informants with the type of research and the approach used was descriptive qualitative. The data collection used was through observation, interview, and documentation techniques. The results showed that the Archives Management at the Office of the Education Quality Assurance Institution/Lembaga Penjaminan Mutu Pendidikan (LPMP) of South Sulawesi Province, was in the effective category, in terms of several indicators of archive management, namely the creation of archives where archives can be created both externally and internally, archive storage is carried out manually using a numbering system and is also carried out digitally, archive maintenance where archives are placed in archival cabinets and archive shrinkage. The results of this study are expected to be used as reference material at the Provincial level institutions because previous research has focused on Regency level institutions